Family history and the natural history of colorectal cancer: Systematic review - Henrikson, N.; Webber, E.; Goddard, K.; Scrol, A.; Piper, M.; Williams, M.; Zallen, D.; Calonge, N.; Ganiats, T.; Janssens, A.; Zauber, A.; Lansdorp_Vogelaar, Iris; et al. (2015)
Purpose: Family history of colorectal cancer (CRC) is a known risk factor for CRC and encompasses both genetic and shared environmental risks. Methods: We conducted a systematic review to estimate the impact of family history on the natural history of CRC and adherence to screening. Results: We found high heterogeneity in family-history definitions, the most common definition being one or more first-degree relatives. The prevalence of family history may be lower than the commonly cited 10%, and confirms evidence for increasing levels of risk associated with increasing family-history burden. There is evidence for higher prevalence of adenomas and of multiple adenomas in people with family history of CRC but no evidence for differential adenoma location or adenoma progression by family history. Limited data regarding the natural history of CRC by family history suggest a differential age or stage at cancer diagnosis and mixed evidence with respect to tumor location. Adherence to recommended colonoscopy screening was higher in people with a family history of CRC. Conclusion: Stratification based on polygenic and/or multifactorial risk assessment may mature to the point of displacing family history-based approaches, but for the foreseeable future, family history may remain a valuable clinical tool for identifying individuals at increased risk for CRC.